Direct emission of nitrous acid (HONO) from gasoline cars in China determined by vehicle chassis dynamometer experiments. (November 2017) - Liu, Yuhan; Lu, Keding; Ma, Yufang; Yang, Xinping; Zhang, Wenbin; Wu, Yusheng; Peng, Jianfei; Shuai, Shijin; Hu, Min; Zhang, Yuanhang
Abstract: HONO plays a key role in atmospheric chemistry, and while its importance is well-known, the sources of HONO are still not completely understood. As a component of ambient HONO sources, direct emission from vehicles is an area that should be extensively studied. In this study, we determined the HONO emission index for typical gasoline vehicles in the car population of China through a chassis dynamometer with different types of engines (PFI/GDI), starting conditions (cold/warm) and running styles (Beijing cycle). Emission ratios of HONO to nitrogen oxide (NOX ) for the Chinese gasoline cars are determined to be in the range of (0.03–0.42) % and an averaged value is about 0.18%, which are comparable to those reported in the few studies available in Europe, the United States and Japan for gasoline cars while smaller for those of the diesel cars. The atmospheric impact of the direct HONO emission from gasoline cars was analyzed for a typical urban site in Beijing, significant contributions of the direct emission toward the HONO budget were found during morning rush hours or twilight conditions to be 8–12%. Graphical abstract: Highlights: HONO emission from Chinese cars is explored with chassis dynamometer experiments. Localized car HONO to NOX emission ratio in China is determined as 0.18%. Car emission contributed significantly toward the HONO budget at urban sites.